Hubungan Tingkat Stres Dengan Efikasi Diri Menyusui Saat Pandemi Covid-19 - Norma Amalia; Dora Samaria (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2021)
Stress can affect a person's self-efficacy in achieving certain goals. A nursing mother who experiences stress has low self-efficacy and low motivation as well as decisions that tend to be negative while facing obstacles in the breastfeeding process. This study was conducted to analyze the relationship between stress levels and self-efficacy of breastfeeding mothers during the COVID-19 pandemic in the Pagiyanten Community Health Center, Tegal Regency, Central Java. This study used a cross sectional research design and was conducted on 75 samples through the total sampling method. Collecting data using the Breasfeeding Self-Efficacy Scale – Short Form (BSES-SF) and Perceived Stress Scale-10 (PSS-10) questionnaires which have been tested for validity and reliability. The results of statistical tests using the chi-square test (p=0.002) showed a relationship between stress levels and self-efficacy of breastfeeding mothers.